Comparative Pacing Profile and Chronometric Performance in Elite Swimmers with Intellectual Impairments and Able-Bodied Athletes - Luca Puce; Piotr Zmijewsk; Nicola Luigi Bragazzi; Carlo Trompetto (Life)
Pacing strategy is a complex self-regulation process, crucial for optimising sports performance. Athletes with Intellectual Impairments (IIs) face unique challenges due to cognitive limitations that may hinder their ability to pace effectively, impacting chronometric performance. This study analysed the pacing profiles and chronometric performance across 253 event entries by elite swimmers with II, divided into three groups: 100 entries for group II1 (intellectual disability), 85 for group II2 (Down syndrome), and 68 for group II3 (autism spectrum disorder). These results were compared with 112 event entries from athletes without disabilities (AWDs). Data were collected from the 2023 Virtus Global Games and the 2023 World Aquatics Championships, focusing on middle-distance and long-distance events. Performance metrics were assessed using 50 m split times, and within-group variability was evaluated through coefficients of variation. Swimmers with IIs showed slower overall chronometric performance than AWDs, with the largest deficits observed in II2 athletes. The II1 and II3 groups displayed more comparable results, with the II1 group outperforming the others slightly. Despite the slower times, pacing profiles were largely similar across all groups, following a parabolic pacing strategy, especially for longer distances. Greater within-group variability in both chronometric performance and pacing profiles was observed in II2 and II3 athletes, reflecting higher functional heterogeneity. In contrast, II1 athletes, and even more so AWDs, exhibited more consistent performance and pacing across all events. While swimmers with II recorded slower times, their pacing strategies resembled those of AWDs, suggesting that cognitive limitations may not significantly impair pacing regulation in swimming. However, the higher variability in II2 and II3 athletes highlights the potential need for revised classification systems to ensure fair competition.